2002
DOI: 10.1002/rcm.881
|View full text |Cite
|
Sign up to set email alerts
|

Study of the attachment of Na+ on glucose and on some of its methylated derivatives

Abstract: The mechanism of attachment of Na(+) on glucose, methyl-alpha-D-glucose, methyl-beta-D-glucose, 3-O-methylglucose, tetra-O-methylglucose, and also on galactose and methyl-beta-D-galactose, was studied. For this we measured the ion yields for the complex [sugar-Na(+)] formed by ionisation by matrix-assisted laser desorption/ionisation (MALDI) and ionspray. These data were compared with the relative volatilities and hydrophobicities of the sugars, measured by evaporative light scattering and reversed-phase liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Another possible explanation for the appearance of the DS vs. DP plot could be that adduct formation with sodium ions is more favourable when methyl groups are present on the oligomer. It has been shown that the ionisation efficiency in MALDI is increased when methyl groups are introduced on glucose and β ‐cyclodextrins 24,25. The fewer methyl groups, the lower the probability of ionisation, and hence the measured DS is higher for short oligomers containing, on average, fewer substituents.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible explanation for the appearance of the DS vs. DP plot could be that adduct formation with sodium ions is more favourable when methyl groups are present on the oligomer. It has been shown that the ionisation efficiency in MALDI is increased when methyl groups are introduced on glucose and β ‐cyclodextrins 24,25. The fewer methyl groups, the lower the probability of ionisation, and hence the measured DS is higher for short oligomers containing, on average, fewer substituents.…”
Section: Resultsmentioning
confidence: 99%
“…The assay of chlorinated species suffers, among others, by the drawback of dealing with multi-isotopic species, whereas the disadvantage of sampling sodiated derivatives is represented by the insufficient sensitivity due, in part, to undesirable multicharged adduct ion formation. [26][27][28][29][30][31] Cesium ions have found important analytical applications and Rogatsky et al [32] have reported a simple, sensitive, and rapid LC-MS/MS method perfectly suited for the analysis of carbohydrates. The latter, detected by ESI (+) as cesium adducts, undergo specific formation of cesium cations at m/z 133 after low energy collision-induced dissociations thus allowing Multiple Reaction Monitoring (MRM) (or Selected Reaction Monitoring (SRM)) monitoring of the given analytes in complex mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Post hoc comparison was performed using Fischer's least significant difference. [26][27][28][29][30][31] Cesium ions have found important analytical applications and Rogatsky et al [32] have reported a simple, sensitive, and rapid LC-MS/MS method perfectly suited for the analysis of carbohydrates. [25] Higher sensitivity is obtained following the fragmentation of [M + NH 4 ] + adducts of saccharides and glucosides.…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanisms about how carbohydrates are alkalized are still unclear. 104) Ion yields of carbohydrates are related to multiple parameters, such as reaction enthalpies for forming adducts with alkali metal ions, volatility, and structural stabilities. 101,105) Owing to the thermally labile nature of carbohydrates, Chen et al reported that low ion yield might be the result of rates of fragmentation and/or desodiation (loss of sodium ions back to its neutral form) being faster than sodiation in the high-temperature ionization environment.…”
Section: Mechanistic Studies Of Carbohydrate Ionization In Maldimentioning
confidence: 99%